2012
DOI: 10.1136/bcr-2012-006846
|View full text |Cite
|
Sign up to set email alerts
|

Psoas abscess secondary to haematoma after a fall causing multiple osteoporotic fractures

Abstract: SummaryA 78-year-old woman presented 28 days after a low-impact fall, where she sustained a right pubic ramus fracture, with increasing left hip pain and fever. Her blood results showed a high white cell count and deranged urea and electrolytes. An MRI revealed multiple osteoporotic fractures and bilateral gluteal abscesses with left iliopsoas abscess, which had likely formed in a haematoma of a sacral fracture. She received a long course of intravenous antibiotics and CT-guided drainage of the abscesses. She … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…1,[4][5][6] Trauma to the iliopsoas muscle, resulting hematoma formation is also a significant risk factor for IPA. 7 Levin et al demonstrated pyomyositis development in injured muscle after administration of intravenous S. aureus. 8 However, iliopsoas hematoma following trauma is very uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…1,[4][5][6] Trauma to the iliopsoas muscle, resulting hematoma formation is also a significant risk factor for IPA. 7 Levin et al demonstrated pyomyositis development in injured muscle after administration of intravenous S. aureus. 8 However, iliopsoas hematoma following trauma is very uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…Iliopsoas abscess can be either primary (without a clear source of infection) or secondary (as a result of direct spread from neighboring structures, such as vertebral bodies and the gastrointestinal tract). The vast majority are caused by Staphylococcus aureus infections [ 2 , 3 ]. Rarely, Mycobacterium tuberculosis can cause a Iliopsoas abscess.…”
Section: Introductionmentioning
confidence: 99%